Pelatihan Penyusunan Laporan Keuangan dalam Meningkatkan Pengetahuan SDM pada Pondok Pesantren Al-Uzlah Madinatul Quran - Budiman Abdulah; Ramdany Ramdany; Ridwan Saleh; Ilza Febrina; Muhammad Syahdam (Jurnal Kabar Masyarakat, 2024)
This community service aims to provide an understanding in preparing financial reports properly and correctly at the AL-UZLAH MADINATUL QUR'AN Islamic Boarding School. The problem faced by partners in this program is the problem of human resource capabilities in managing financial data into financial reports. The method of implementing this entrepreneurship-based empowerment uses the Participatory Action Research (PAR) method, starting from the socialization stage at the beginning of the community service activity, in the form of providing information to partners/communities about the community service activities to be carried out, the objectives of the activity, the stages of implementing the activity, and the schedule for implementing the activity based on an agreement between the proposing team and partners, the next stage is training and mentoring and evaluation of the activity. The results of the activity showed an increase in partner knowledge regarding the preparation of financial reports before and after training.